HGG-25. INFANT GLIOMAS COMPRISE MULTIPLE BIOLOGICAL AND CLINICOPATHOLOGICAL SUBGROUPS. Issue 2 (22nd June 2018) - Clarke, Matthew T; Jones, David TW; Mackay, Alan; Carvalho, Diana; Izquierdo, Elisa; Hiddingh, Lotte; Temelso, Sara; Burford, Anna; Molinari, Valeria; Boult, Jessica KR; Virasami, Alex; Carceller, Fernando; et al.
Abstract: Infant gliomas have been considered as early-onset examples of tumour types found throughout paediatric populations. Interestingly, infant high-grade gliomas (HGG) have a better overall survival compared to older children, indicating that grading may not accurately reflect the biology of these tumours. We have to-date collected 181 cases of diffuse glioma (WHO II-IV) occurring in children aged <4 years for histological review, methylation profiling, gene fusion panel and whole genome/exome sequencing. Of 147 samples profiled using the Heidelberg methylation classifier, 20 were reassigned as established brain tumour entities (e.g. pilocytic astrocytoma, HGNET-BCOR), whilst a further 23 fell into recognised HGG subgroups. The remaining 104 cases formed four distinct subgroups by consensus clustering. Two groups were mostly classified as 'infantile hemispheric gliomas' (IHG), one of these showing enrichment for ALK/NTRK fusion genes, the other a male predominance, and both with a median age ≤1 year. IHG had a highly cellular, uniform architecture with gemistocytic-like or spindle cell morphology. A third group did not fit with established methylation subgroups but were largely female, ≤6 months, and harboured ALK/NTRK fusions. The fourth group were older, comprising desmoplastic infantile gliomas and poorly-scoring cases of other low-grade tumours. We established three novel patient-derived cultures of IHG, with TPM3:NTRK1, KCTD16:NTRK2 and ETV6:NTRK3 fusions. Drug screening with multiple NTRK inhibitors revealed marked sensitivity in vitro, making such patients excellent candidates for clinical trials of these compounds. The clinical, histological and molecular features of infant gliomas suggest the presence of novel tumour subgroups, which may have targetable driving alterations.